NullHap – a versatile application to estimate haplotype frequencies from unphased genotypes in the presence of null alleles - Płoski Rafał; Nowak Robert M (BMC Bioinformatics, 2008)
Abstract Background Laboratory techniques used to determine haplotypes are often too expensive for large-scale studies and lack of phase information is commonly overcome using likelihood-based calculations. Whereas a number of programs are available for that purpose, none of them can handle loci with both multiple and null alleles. Results Here we present a description of a modified Expectation – Maximization algorithm as well as its implementation (NullHap) which allow to effectively overcome these limitations. As an example of application we used Nullhap to reanalyze published data on distribution of KIR genotypes in Polish psoriasis patients and controls showing that the KIR2DS4/1D locus may be a marker of KIR2DS1 haplotypes with different effects on disease susceptibility. Conclusion The developed application can estimate haplotype frequencies for every type of polymorphism and can effectively be used in genetic research as illustrated by a novel finding regarding the genetic susceptibility to psoriasis.